Real estate investment strategies for foreign investors: regulatory barriers and market opportunities - Sanchez, Maria Isabel (Revista JRG de Estudos Acadêmicos, 2025)
This narrative review, based on a qualitative and interpretive approach, examines regulatory barriers and market opportunities related to foreign real estate investment. A comprehensive yet non-systematic search was conducted in Scopus, Web of Science, PubMed, and SciELO for peer-reviewed studies published between 2015 and 2025 in Portuguese, English, and Spanish. Eligible articles addressed non-resident investors and at least one of the following: price dynamics, transaction volumes, rents, housing supply/stock, or affordability, as well as policy instruments such as foreign-buyer surcharges, ownership restrictions or bans, residency-by-investment programs, and capital controls. Screening proceeded in two stages (titles/abstracts and full texts), and findings were synthesized through thematic analysis using a standardized evidence chart. Results indicate that surcharges targeted at non-resident buyers tend to moderate prices in the short term, with heterogeneous magnitude across segments and locations; residency-by-investment schemes show modest aggregate impacts but can create localized heating near eligibility thresholds; inbound-oriented capital controls may dampen cycles depending on domestic financial settings; and increased foreign participation often pressures upper-tier segments without a proportional supply response. The review concludes that policy mixes combining selective demand-side instruments with supply-expanding measures and granular monitoring by segment and territory are more likely to foster market stability and affordability. Limitations inherent to narrative designs were mitigated through explicit search, selection, and qualitative appraisal criteria.